Geophysical investigation of earth dam using the electrical tomography resistivity technique - Camarero, Pedro Lemos; Moreira, Cesar Augusto (Fundação Gorceix, 2017)
Abstract Dams are structures that dam rivers and streams for a variety of purposes. These structures often need to be sturdy to withstand the force of the impoundment and the high values of accumulated water load. The constant maintenance of these structures is essential, since a possible accident can lead to damage of catastrophic proportions. This research presents an alternative cheap and quick application for investigating water seepage in earth dams, through the application of the DC resistivity geophysical method from the electrical resistivity tomography (ERT) technique in Wenner array. Three ERT lines were placed parallel to the longitudinal axis of a dam formed by clay soil from the decomposition of diabase. The data are presented in 2D and pseudo-3D geophysical images with electrical resistivity values modeled. Based on the physical principle of electrolytic conduction, that is, decrease in electrical resistance in materials or siliceous minerals in moisture conditions as compared to the material in the dry state, the results revealed low-resistivity zones restricted to some points, associated with water infiltration in the transverse direction of the dam. The absence of evidence as water upwelling on the front of the dam together with geophysical evidence indicate saturation restricted to some points and low probability at the present time, for installation of piping processes.
Keywords: internal erosion; geophysics; dams; electrical resistivity